An empirical analysis of the utilization of new media in sports science - Samson, T.; Igel, C.; Meiers, R. (International Journal of Computer Science in Sport, 2006)
The present study is intended to provide a cause and effect analysis of the degree of penetration of new media in university fields of competence and activity at the institutes of sports science and sport in Germany. The analysis focuses on the area of "Studies and Extended Studies", but also considers the fields of "Research and Development" and "Administration and Management".